2020
DOI: 10.21203/rs.3.rs-41684/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nomogram to identify severe Coronavirus Disease 2019 (COVID-19) based on initial clinical and CT characteristics: a multi-center study

Abstract: Background: To develop and validate a nomogram for early identification of severe coronavirus disease 2019 (COVID-19) based on initial clinical and CT characteristics.Methods: The initial clinical and CT imaging data of 217 patients with COVID-19 were analyzed retrospectively from January to March 2020. 217 patients with 146 mild cases and 71 severe cases were randomly divided into training and validation cohorts. Independent risk factors were selected to construct the nomogram for predicting severe COVID-19. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Area of consolidation, bronchiectasis and traction bronchiectasis were significantly more often found in the severe group of patients. In line with some other studies, air bronchogram sign [13,17] and pleural effusion [17] were also significantly more often found. Unlike in some other studies, pericardial effusion was not found as a criteria associated with a severe form, nor was lymph node enlargement, nor was crazy-paving pattern [13,17].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Area of consolidation, bronchiectasis and traction bronchiectasis were significantly more often found in the severe group of patients. In line with some other studies, air bronchogram sign [13,17] and pleural effusion [17] were also significantly more often found. Unlike in some other studies, pericardial effusion was not found as a criteria associated with a severe form, nor was lymph node enlargement, nor was crazy-paving pattern [13,17].…”
Section: Discussionsupporting
confidence: 91%
“…In line with some other studies, air bronchogram sign [13,17] and pleural effusion [17] were also significantly more often found. Unlike in some other studies, pericardial effusion was not found as a criteria associated with a severe form, nor was lymph node enlargement, nor was crazy-paving pattern [13,17]. The most relevant CT features were all related to the extent of the disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations